Tuning the Mechanical Properties of Hydrogel Core-Shell Particles by Inwards Interweaving Self-Assembly - Pan, Houwen Matthew; Seuss, Maximilian; Neubauer, Martin P.; Trau, Dieter W.; Fery, Andreas (ACS Applied Materials and Interfaces, 2016)
Mechanical properties of hydrogel particles are of importance for their interactions with cells or tissue, apart from their relevance to other applications. While so far the majority of works aiming at tuning particle mechanics relied on chemical cross-linking, we report a novel approach using inwards interweaving self-assembly of poly(allylamine) (PA) and poly(styrenesulfonic acid) (PSSA) on agarose gel beads. Using this technique, shell thicknesses up to tens of micrometers can be achieved from single-polymer incubations and accurately controlled by varying the polymer concentration or incubation period. We quantified the changes in mechanical properties of hydrogel core-shell particles. The effective elastic modulus of core-shell particles was determined from force spectroscopy measurements using the colloidal probe-AFM (CP-AFM) technique. By varying the shell thickness between 10 and 24 μm, the elastic modulus of particles can be tuned in the range of 10-190 kPa and further increased by increasing the layer number. Through fluorescence quantitative measurements, the polymeric shell density was found to increase together with shell thickness and layer number, hence establishing a positive correlation between elastic modulus and shell density of core-shell particles. This is a valuable method for constructing multidensity or single-density shells of tunable thickness and is particularly important in mechanobiology as studies have reported enhanced cellular uptake of particles in the low-kilopascal range (<140 kPa). We anticipate that our results will provide the first steps toward the rational design of core-shell particles for the separation of biomolecules or systemic study of stiffness-dependent cellular uptake.
CRIS-Team Scopus Importer:2023-03-20
Keywords: agarose; atomic force microscope; elastic modulus; hertz model; layer-by-layer assembly; microparticles